2009
DOI: 10.17221/1662-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Results of pig carcass classification according to SEUROP in the Czech Republic

Abstract: Pigs and dairy cows are the two main industries of livestock production in the Czech Republic (CR) and in the European Community (EC) as a whole. Of the total annual per capita meat consumption in the CR (81 kg), in the EC (92 kg) and worldwide (42 kg) pig meat accounts for 54% (43.5 kg), 47% (42.7 kg) and 39% (16.4 kg), respectively. Longterm forecasts indicate that the production and consumption of pig meat in the EC will slowly grow by about 3% to 4% by 2013. In accordance with the common agricultural polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
2
11
1
Order By: Relevance
“…The longest calving interval was associated with the highest loss of calves and the lowest number of the total weaned calves per 100 cows (P < 0.05). Kvapilík et al (2013) reported similar findings that longer calving intervals (above the optimal of 400 d) decreased the average daily milk yield in the herd and smaller numbers of calves. For herds with a poor reproductive performance, Dono et al (2013) found that the economic advantage of shortening the mean calving interval by removing cows from the herd that failed to conceive was outweighed by the costs associated with the increased herd turnover.…”
Section: Optimal Calving Interval and Profitsupporting
confidence: 54%
See 1 more Smart Citation
“…The longest calving interval was associated with the highest loss of calves and the lowest number of the total weaned calves per 100 cows (P < 0.05). Kvapilík et al (2013) reported similar findings that longer calving intervals (above the optimal of 400 d) decreased the average daily milk yield in the herd and smaller numbers of calves. For herds with a poor reproductive performance, Dono et al (2013) found that the economic advantage of shortening the mean calving interval by removing cows from the herd that failed to conceive was outweighed by the costs associated with the increased herd turnover.…”
Section: Optimal Calving Interval and Profitsupporting
confidence: 54%
“…Kvapilík et al (2013) reported that even as the average farm milk price in the Czech Republic during 2012 was 7.67 CZK/l milk, the average of the total cost was 9.14 CZ/KL of milk, and the total costs minus the indirect costs (i.e., the costs of rearing calves, the costs of manure disposal) were 8.73 CZK/L of milk. It is evident that dairy farms in the Czech Republic would be operating at a loss without subsidies (Table 3).…”
Section: Reasons For Culling Cowsmentioning
confidence: 99%
“…In our study, the percentage contents of fat and protein in milk were the lowest in the highest MY group (protein 3.38 ± 0.03% and fat 3.84 ± 0.05%). Kvapilík et al (2013) have reported that the average farm milk price in the Czech Republic during 2012 was 7.67 CZK/L of milk while the average of the total costs was 9.14 CZK/L of milk. The average costs excluding indirect costs (i.e., the costs of rearing calves, the costs of manure disposal) were 8.73 CZK/L of milk.…”
Section: High-producing Dairy Herdmentioning
confidence: 99%
“…Increasing milk yields leave the total cost per L and net margin per L relatively unchanged, but the increased milk output substantially boosts the herd's total profit (Buza et al, 2014). Kvapilík et al (2013) and Heikkilla et al (2008) found that the price movements for milk, the components in milk, and the production inputs can significantly affect the farm profitability and that the management should therefore adapt to these changes.…”
Section: High-producing Dairy Herdmentioning
confidence: 99%
“…The average revenues per animal sold reduced by the percentage of death losses were either excluded or included, respectively) (Kvapilík et al, 2015). The return on costs determined for fattening operations in the report by Kvapilík et al (2015) was -3.3 % and thus by 1.5 and 10.4 percentage points higher (smaller loss) than those observed in our study for 2013 and 2014, respectively. In 2005, the loss calculated per 1 kg of live slaughter weight of bulls was 1.09 CZK (Kopeček et al, 2009).…”
Section: Calculation Of Profitabilitymentioning
confidence: 70%